Los ambientes pedagógicos para el mejoramiento de la enseñanza aprendizaje de los niños y niñas de la educación inicial del centro de sabiduría infantil “Mushuk Muyitukuna” de la comunidad anguiñay parroquia Pungala, cantón Riobamba provincia Chimborazo en el año lectivo 2010 – 2011 - Chucuri Sayay, José Francisco (2011)
Our research is based on the need to know the educational environment for the improvement of teaching and learning of children in Early Education Child Center of wisdom "MushukMuyitukuna" Anguiñay parish community Pungal Region Riobamba Chimborazo province in the Year school year 2010 - 2011, to seek a quality education, allowing children to be dynamic, critical, reflective, creative, where they can express their thoughts, feelings, emotions and ideas through educational environments. The central problem of this study was the lacks of educational environments do not allow the improvement of teaching and learning of children in Early Education Center Children's Wisdom "MushukMuyitukuna" meaning that there is no use of environmental materials and recycling. As one of the objectives for the study was to strengthen the educational environment through the collection of materials for each of the environments. Within the research the following hypothesis was proposed, with the work of educational environments enhances teaching and learning of children in early childhood education Child Center of Wisdom "MushukMuyitukuna" the same as it was proven that educational environments are critical in the development of teaching and learning of children. The methodology is applied in the conduct of research, is associated with the resources and processes that led to its procedure for the different methods applied análisis.Se as: inductive, deductive, descriptive, scientific literature, the instruments were applied: the survey of parents and teachers and observing the children in school education. To the solution was collected teaching materials for each of the environments, educational theories, educational, cognitive, experimental, in which were based educational environments, propose the implementation and management of learning environments for teaching at the center of MUYITYKUNA Mushuk child wisdom. In conclusion it was stated that teachers and children have no knowledge of educational learning environments for teaching learning and development of thought. After the research has been found to lack implementing pedagogical learningenvironments to produce effect on teaching and learning of children of preschool children wisdom center MuyitukunaMushukAnguiñay Community of Chimborazo province, Riobamba canton, Parish Pungal, in the year 2010 - 2011 As a recommendation should encourage teachers about the need for the use of educational environments. Socialize guidance through demonstration classes for the teacher to implement different strategies when necessary. To deepen the knowledge of educational environments that can be applied correctly according to the individuality of the boy and girl. Use every day to evaluate different strategies for learning educational environments.